On the Relation Between Income Inequality and Economic Growth: An Asymmetric Analysis - (:unkn) unknown (My University, 2018)
Economic growth and income inequality are two prominent topics in development economics due to their close relation to social stability. The main objective of this thesis is to investigate the short-run and long-run dynamics between income inequality and income growth. Additionally, it is important to consider the dynamic between income inequality and income volatility. This investigation fills a gap in the literature by examining whether changes in income, as well as changes in income volatility, have asymmetric effects on income distribution. The study of asymmetric impacts is critical because it might not be always true that economic booms and busts have similar effects in terms of magnitudes and signs on income disparity. To conduct the analysis, country-level data was obtained for forty countries from two sources for the time periods ranging from 1963-2008: (1) University of Texas Inequality Project and (2) the International Financial Statistics of the International Monetary Fund. State-level data were obtained for all fifty US states for 1945-2013 from a construction of the Internal Revenue Service data set by Frank (2009). To determine the short-run and long-run dynamics between income inequality and income growth, the Linear Autoregressive Distributive Lag (ARDL) approach to cointegration and the Non-linear Autoregressive Distributive Lag (NARDL) approach are employed. Results from both country and state level data suggest an asymmetric relationship between income inequality and its determinants. In the other words, income growth and income volatility have long-run asymmetric impacts on the distribution of income. In almost all the cases that the long-run relationships are established, increased and decreased per capita income, also increased and decreased income volatility hurt income distribution.
Keywords: Asymmetric Analysis; Economic Growth; Income Inequality